2000
DOI: 10.1063/1.1309019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of in-plane anisotropic strain on the polarization behavior of vertical-cavity surface-emitting lasers

Abstract: Articles you may be interested inControlled switching of ultrafast circular polarization oscillations in spin-polarized vertical-cavity surface-emitting lasers Appl. Phys. Lett.Interpretation of polarization pinning due to scattering loss differentiation in asymmetric vertical-cavity surfaceemitting laser cavities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(58 citation statements)
references
References 11 publications
2
56
0
Order By: Relevance
“…28 Second Panajotov et al reported control of VCSEL polarization and cavity anisotropies through application of strain on the VCSEL mounting. 29 …”
mentioning
confidence: 99%
“…28 Second Panajotov et al reported control of VCSEL polarization and cavity anisotropies through application of strain on the VCSEL mounting. 29 …”
mentioning
confidence: 99%
“…Another future line consists in changing the birefringence of the VCSEL sample, varying the distance in the central wavelength of both sub-combs and increasing also the modulation frequency range available. Experiments like this have been previously done in works like [18].…”
Section: Discussionmentioning
confidence: 99%
“…A prominent manifestation of the resulting polarization instabilities is the phenomenon of polarization switching, [2][3][4][5][6][7][8][9] i.e. a sudden change to the linear state of polarization oriented orthogonally to the one selected at threshold, if the current surpasses a critical value.…”
Section: Introductionmentioning
confidence: 99%
“…These modes will, in general, also have a slightly different net gain (net gain = unsaturated gain -unsaturated losses), which results in the selection of the favored mode at threshold. 3 In this paper, the term 'dichroism' will be used to denote the resulting net gain anisotropy that results from various effects like mechanical stress, 3,7,12 anisotropic losses in the Bragg mirrors of the VCSELs 13 and gain differences for the polarization modes due to the different material gain that is caused by the different positions of the modes on the gain curve. 3 However, even at threshold the selection of the polarization state is not perfect in every device and under every operating condition.…”
mentioning
confidence: 99%